Effectiveness of Structural Teaching Program on Knowledge, Attitude and Practice (KAP) Regarding Breast Cancer and Breast Self-Examination (BSE) Among Undergraduate Nursing Students - Pardhan, Shahla; Mendhrani, Srikant; Mohmand, Zarmina; Bibi, Anila; Afzal, Larib; Fatima, Sana; Solangi, Tayyaba; Michael, Aliza; Khan, Khairunnisa (Biological and Clinical Sciences Research Journal, 2025)
Globally, breast cancer is primary cause of morbidity and mortality, reducing life by over 18.5 years. Annually, 1,384,155 cases were diagnosed globally. Therefore, Breast Self-Examination (BSE) is cost-free & non-invasive, and private method for women to identify potential breast health issues. Objective: To assess and evaluate the Knowledge, Attitude and Practices (KAP) amongst undergraduate nursing student’s about Breast Self-Examination. Methods: A Quasi Experimental Study was conducted in two public and one Private Nursing Colleges which were residing in Karachi, Pakistan, where data collected amongst 383 female undergraduate Nursing students, from June, 2024 to January, 2025 to assess the KAP amongst them. Results: The majority of participants were aged 18–20 years (54.6%), single (88.8%), and lived in urban areas (64%). Most were first-year students (55.6%) and Mothers’ education levels varied, with (36%) having no formal education. Only (10.2%) reported a family history of breast cancer. Awareness and knowledge of BSE improved significantly after the intervention. Awareness rose from (60.8% to 91.6%) (p = 0.001). Correct knowledge about starting BSE at age 20 increased from (17% to 82.2%), and monthly practice rose from (29.5% to 81.7%) (Both p < 0.001). More participants correctly identified the ideal time for BSE as a week after menstruation (19.3% to 85.6%, p < 0.001), though the intervention significantly improved attitudes toward BSE rose from (30% to 77.5%) (p = 0.001), fear of seeing a doctor decreased (p = 0.016), family and community support for BSE increased from (7.8% to 54.8%) (p = 0.011). Similarly, the intervention significantly improved participants' practice of BSE rose from (23% to 73.1%) (p = 0.011), while ignorance as a reason for not practicing dropped from (81.8% to 11.7%) (p = 0.021), Fear of finding a lump increased post-intervention (2.6% to 75.7%), showing heightened awareness, and Knowledge of correct techniques improved notably: inspecting in front of a mirror (26.1% to 93.2%), using middle three fingers (30.8% to 77.5%), and the opposite hand (83.8%). Understanding of examining the armpit and identifying nipple discharge errors also improved, and correct rejection of the triangular method increased from (23.2% to 87.7%) (p = 0.011) respectively. Conclusion: The intervention significantly enhanced Positive attitudes towards BSE increased with a higher percentage of participants recognized its importance, Fear of discovering a lump decreased, although perceptions regarding discomfort also showed minimal change.